2021
DOI: 10.1177/08919887211016057
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cognitive and Physical Training Effectiveness in MCI, Based on the Experience of the Alzheimer’s Hellas Day Care Centre

Abstract: This study assesses the effectiveness of a multicomponent Longitudinal Cognitive Training (CT) program plus physical exercise (PE) for people with Mild Cognitive Impairment (MCI). 155 people with MCI, completed a 3 years (3Y) CT+PE, whilst 133 were control. Neuropsychological assessment was performed at baseline and 3 years later, whilst CT+PE had additional annual assessments. According to the results, the 3Y CT+PE outperformed control in cognitive abilities ( p < 0.002), and Activities of Daily Living (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…First, our findings highlight the significance of implementing meaningful activities and psychosocial web-based interventions in older adults with MCI as well as ADD in mild and moderate stages, which is also in line with previous evidence [6,14]. Our recent study [41] was partially in line with the current results because we found that deterioration was increased in the MCI population by means of measuring their long-term memory with RAVLT as well as the phonemic verbal test. Therefore, it could be assumed that MCI participants' performance, at least as measured by the aforementioned tests, is not affected by the quarantine.…”
Section: Discussionsupporting
confidence: 92%
“…First, our findings highlight the significance of implementing meaningful activities and psychosocial web-based interventions in older adults with MCI as well as ADD in mild and moderate stages, which is also in line with previous evidence [6,14]. Our recent study [41] was partially in line with the current results because we found that deterioration was increased in the MCI population by means of measuring their long-term memory with RAVLT as well as the phonemic verbal test. Therefore, it could be assumed that MCI participants' performance, at least as measured by the aforementioned tests, is not affected by the quarantine.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, due to the increasing number of people suffering from dementia, brain exercise interventions and delaying cognitive decline in people with MCI have gained considerable attention [ 59 ]. Recent longitudinal findings suggest that structured cognitive interventions can target brain function by increasing cognitive reserve and thus delay the progression of MCI [ 15, 59, 61–63 ]. E.L.So.M.C.I.…”
Section: Discussionmentioning
confidence: 99%
“…59 One study found that 3 years of following a cognitive and physical training intervention seemed to reduce the number of people with MCI who progressed to dementia. 60 New technologies are emerging quickly, and can take on multiple roles; for example, a cognitive training application based on a virtual shopping task not only strengthens memory, planning, and other cognitive skills, but can also be used to screen for MCI. 61,62 The Virtual Supermarket (VSM) test is multilingual and fully self-administered in its latest iteration.…”
Section: Challenges In Dementia Care: Regional Policies and Initiativesmentioning
confidence: 99%
“…In Greece, cognitive stimulation, rehabilitation, and training programs are delivered in day centers 59 . One study found that 3 years of following a cognitive and physical training intervention seemed to reduce the number of people with MCI who progressed to dementia 60 …”
Section: Challenges In Dementia Care: Regional Policies and Initiativesmentioning
confidence: 99%